IMPLEMENTATION OF MUDHARABAH IN BANK SYARIAH INDONESIA: IMPACT ON ECONOMIC GROWTH - Jojo Jojo; Ana Frasipa; Dira Alfa Rizky; Mira Nurul Aghniya (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
This study analyzes the implementation of Mudharabah contracts at Bank Syariah Indonesia (BSI) and their impact on economic growth. As a profit-sharing model, Mudharabah has great potential to promote equitable and sustainable development, particularly through the empowerment of MSMEs. Using a descriptive–qualitative method, this research draws on secondary data from journals and articles indexed in Google Scholar and ScienceDirect. Findings indicate that the limited application of Mudharabah is due to high financial risks for banks (shahibul maal) and moral hazard risks from business managers (mudharib). When effectively applied, Mudharabah supports the real sector, expands financial inclusion, and promotes macroeconomic growth. Strengthening digital-based risk management, fintech collaboration, portfolio realignment, and regulatory support are recommended to enhance its effectiveness.